Determinants of dividend payout: a study on Malaysian companies / Norhafila Norashikin - Norashikin, Norhafila (Faculty of Business and Management, 2007)
This study investigates on the determinants of dividend payout on Malaysian companies. Specifically, the sample for this study is 40 selected companies from 100 KLCI components. The estimation period for this study is from 2000 to 2005. In this study, the dividend payout is considered as the dependent variable while the independent variables are investment opportunities, leverage and size of firm. In measuring the relationship, Multiple Regression Model is used for this study. Based on the findings, there is no significant relationship between dividend payout with investment opportunities, leverage and size of firm.